2021
DOI: 10.1111/jfbc.13830
|View full text |Cite
|
Sign up to set email alerts
|

Lagerstroemia speciosa (L.) Pers., ethanolic extract attenuates simultaneously administered isoniazid‐ and dapsone‐induced hepatotoxicity in rats

Abstract: Herbal tea of Lagerstroemia speciosa Pers., commonly known as banaba, has been traditionally used to treat various ailments including diabetes and obesity due to its antioxidant and anti‐inflammatory efficacies. Drug‐induced liver injury is a common cause of acute liver failure. Isoniazid (INH) is used as the first‐line treatment for tuberculosis; clinical and experimental studies have reported an abnormal liver function after INH therapy. Dapsone (DDS) is used for leprosy and other infections. This study inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Several commonly used drugs in clinical practice are responsible for DILI and are often manifested as liver inflammation and necrosis 1 . For instance, acetaminophen, amoxicillin/clavulanate, dapsone, isoniazid and methotrexate are the most common causes of DILI 2–4 . DILI can be classified as predictable and unpredictable or idiosyncratic.…”
Section: Introductionmentioning
confidence: 99%
“…Several commonly used drugs in clinical practice are responsible for DILI and are often manifested as liver inflammation and necrosis 1 . For instance, acetaminophen, amoxicillin/clavulanate, dapsone, isoniazid and methotrexate are the most common causes of DILI 2–4 . DILI can be classified as predictable and unpredictable or idiosyncratic.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that the presence of berberine and gallic acid in a plant as phytocompounds might protect the liver from drug and chemicalinduced liver injuries. 42,43 As pure compounds, both berberine and gallic acid administration offer membrane stabilizing properties, thereby protecting against drug and chemical-induced liver injury. 44,45 In this study, concurrent TAA + CVERE and TAA + SIL treatments significantly inhibited the elevation of serum marker enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The present study also showed increased serum liver marker enzyme activities upon TAA administration. Studies have reported that the presence of berberine and gallic acid in a plant as phytocompounds might protect the liver from drug and chemical‐induced liver injuries 42,43 . As pure compounds, both berberine and gallic acid administration offer membrane stabilizing properties, thereby protecting against drug and chemical‐induced liver injury 44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…DILI is normally a dose-related phenomenon; however, it can also occur in the context of therapeutic doses. DILI occurs in a significant number of people exposed to drugs and generally is a challenging task for diagnosis and drug development [1]. More than a thousand drugs used in clinical practice are suspected to induce liver damage, of which 353 medications were convincingly related to liver injury [2].…”
Section: Introductionmentioning
confidence: 99%